2017
DOI: 10.17265/2161-6213/2017.5-6.002
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Elastomer Transducer Driven by Karman Vortices in Water Flow

Abstract: A simple experimental model of a power generation system was tested in a flowing water tank in order to investigate the performance and feasibility of a small hydroelectric generation system using DE (dielectric elastomer) transducer. The mass of DE material in the power generator module was only 0.1 g. The electric energy generated with a stroke of 10 mm was 12.54 mJ. An electrical energy of approximately 1.5 J per cycle of DE generators can be expected to be generated by scaling up this system, which is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Next, regarding the DEG using water flow, it was found that even a fairly slow flow (0.30 m/s to 0.70 m/s.) can sufficiently generate electricity using karma vortices [72]. With this system, it is possible to use the height difference of the water, and it is possible to easily generate power even in waterways beside rice fields.…”
Section: Use Of Wave Power and Water Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, regarding the DEG using water flow, it was found that even a fairly slow flow (0.30 m/s to 0.70 m/s.) can sufficiently generate electricity using karma vortices [72]. With this system, it is possible to use the height difference of the water, and it is possible to easily generate power even in waterways beside rice fields.…”
Section: Use Of Wave Power and Water Flowmentioning
confidence: 99%
“…The method [72] for generating electricity using vibration is also a useful means, but effective power generation cannot be obtained unless the vibration is large or fast. Research and development of wearable power generation by attaching DEs to humans, robots, and animals is also underway [50].…”
Section: Degs Using Renewable Energy Other Than the Abovementioning
confidence: 99%
“…Home-sized wind turbines are being studied as a point application for DEGs [37,42,43]. A type using the Kalman style is possible with high efficiency.…”
Section: Background Of the Deg Systemmentioning
confidence: 99%
“…Chiba et al conducted wave tests using experimental models from 2011 to 2015 in order to investigate the power generation characteristics of buoy type power generation systems equipped with DEs and measured the power generation amounts for various wave heights and wave periods [22][23][24][25][26]. The power generation device using the DE has a simple structure and is lightweight, so that it is expected that the wave power generation system can be simplified, lightened and miniaturized.…”
Section: David Publishingmentioning
confidence: 99%
“…The power generation device using the DE has a simple structure and is lightweight, so that it is expected that the wave power generation system can be simplified, lightened and miniaturized. They also considered aggregates of buoys, arrays of buoys with 3 dimensional multi-story DEs, and the spring constant of the DE in order to realize large power generation system in actual sea areas using the DEs [22][23][24][25][26][27][28].…”
Section: David Publishingmentioning
confidence: 99%